EMCO WinNC for Fanuc 31i Mill: Software description WinNC for Fanuc 31i Mill : (Ref.no.EN 1846- Edition B2026-06) - EMCO group (EMCO group, 2015)
The EMCO WinNC for Fanuc 31 i software is a component of the EMCO training concept. EMCO WinNC for 31i makes it easy to operate CNC lathes/Milling machines. Neither is prior knowledge of ISO programming needed. An active contour programming routine means you can define workpiece contours with linear and circular contour elements. A cycle is programmed interactively, with graphics support. A large number of processing cycles, wich can be combined freely with each other to form a single program, is available to the user. Individual cycles ro the NC programs produced can be simulated graphically on screen. Some of the fuctionality of the EMCO WinNC for Facuc 31i control software is beyond the scope of these instructions. Emphasis is placed instead on representing the greatest possible learning success.